(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This study focuses on using consumer motivation to encourage the adoption of cleaner technologies. Consumers are varied since they may be driven by internal or external reasons. Though information provision methods may be helpful in encouraging some consumers to purchase electric vehicles. Also, financial incentive schemes such as discounts or penalties may be more persuasive to extrinsically driven customers. This article offers a sophisticated theory of environmental innovation adoption in which information-provision methods are complemented with economic incentives. The different studies have been done to find out the policies for encouraging customers to reduce the harmful impacts of transportation system on environment. The projection of electric cars sales by 2030 is examined. Finally, the different reasons fueling development of electric cars are explored in depth. The results of this study would be of particular relevance to legislators who seek to push consumers toward greener technologies.